A new species of Demonax Thomson (Coleoptera: Cerambycidae: Cerambycinae) from Southwest China, with a key to thirteen species from China - Li, Zhu; Tian, Li-Chao; Chen, Li (Zootaxa, 2013)
A new species, Demonax proculscuti Li, Tian & Chen, sp. nov. (Coleoptera: Cerambycidae: Cerambycinae), is described from Yunnan Province, Southwest China. A key to 13 species of Demonax from China is presented.